Use of cross-reactivity immunoassay to orient insulin replacement in diabetic patients with high levels of insulin antibodies - Cardoso Landaburu, Alejandro Cesar (2016)
The prevalence and high levels of anti-insulin antibodies (IA) have frequently been associated with brittle diabetes, lipodystrophy in the areas where the insulin is injected and/or poor metabolic control. When this happens the usual criterion adopted is the empirical change of insulin type and/or formulation intending to diminish the IA level and then to decrease the undesirable side-effects. Here, we present a rational two step radiometric method consisting in: A) a first-line radioligand binding assay (RBA) to assess IA in sera of these patients and detecting those with high levels. B) applying a displacement assay (RIA) to determine the in vitro cross-reactivity parameters (affinity constants and selectivity ratios) that quantify the relative degree of interaction between antibodies and alternative insulin analogs. From these results we conclude that conventional criteria for selection of insulin analogs, in terms of pharmacokinetic and pharmacodinamic parameters, should be complemented with an appropriate test to assess affinity parameters when high IA title is demonstrated. • This manuscript introduces a rational method to determine the appropriated insulin replacement when high insulin antibodies levels are present.• This protocol provides instructions and details in mathematical tools and laboratory processes for the analysis of serum samples.• This method proved to be successful in a single case and requires confirmation using a large group of patients.